Review of the Eumerus tricolor species group (Diptera: Syrphidae) in Iran, with description of six new species - Gilasian, Ebrahim; van Steenis, Jeroen; Parchami-Araghi, Mehrdad (European Journal of Taxonomy, 2020)
The species of the Eumerus tricolor species group in Iran are reviewed. Six species new to science are described from Iran, i.e., Eumerus atricolorus Gilasian & van Steenis sp. nov., E. brevipilosus Gilasian & van Steenis sp. nov., E. chekabicus Gilasian & van Steenis sp. nov., E. ovoformus Gilasian & van Steenis sp. nov., E. pilosipedes Gilasian & van Steenis sp. nov. and E. vallicolus Gilasian & van Steenis sp. nov. Three species, E. hissaricus Stackelberg, 1949, E. longitarsis Peck, 1979 and E. richteri Stackelberg, 1960, are newly recorded from Iran. Photographs of the species as well as illustrations of the male genitalia of the new species and closely related species are provided. An identification key to the males of the Iranian Eumerus tricolor species group is presented. A row of long posterodorsal setae on the wing vein costa basally is presented and argued as a new diagnostic morphological character for the entire Eumerus tricolor species group.